Consensus guideline for the diagnosis and treatment of aromatic l-amino acid decarboxylase (AADC) deficiency. Issue 1 (December 2017) - Wassenberg, Tessa; Molero-Luis, Marta; Jeltsch, Kathrin; Hoffmann, Georg; Assmann, Birgit; Blau, Nenad; Garcia-Cazorla, Angeles; Artuch, Rafael; Pons, Roser; Pearson, Toni; Leuzzi, Vincenco; Mastrangelo, Mario; et al.
Abstract Aromatic L-amino acid decarboxylase deficiency (AADCD) is a rare, autosomal recessive neurometabolic disorder that leads to a severe combined deficiency of serotonin, dopamine, norepinephrine and epinephrine. Onset is early in life, and key clinical symptoms are hypotonia, movement disorders (oculogyric crisis, dystonia, and hypokinesia), developmental delay, and autonomic symptoms. In this consensus guideline, representatives of the International Working Group on Neurotransmitter Related Disorders (iNTD) and patient representatives evaluated all available evidence for diagnosis and treatment of AADCD and made recommendations using SIGN and GRADE methodology. In the face of limited definitive evidence, we constructed practical recommendations on clinical diagnosis, laboratory diagnosis, imaging and electroencephalograpy, medical treatments and non-medical treatments. Furthermore, we identified topics for further research. We believe this guideline will improve the care for AADCD patients around the world whilst promoting general awareness of this rare disease. German abstract Der Aromatische L-Aminosäuren Decarboxylase Mangel (AADCD) ist eine seltene autosomal rezessive neurometabolische Störung, die zu einem schweren kombinierten Mangel an Serotonin, Dopamin, Norepinephrin und Epinephrin führt. Die Symptome setzen in einer frühen Phase des Lebens ein. Die klinischen Hauptsymptome sind muskuläre Hypotonie, Bewegungsstörungen (Okkulogyre Krisen, Dystonie und Hypokinesie), Entwicklungsverzögerung und autonome Symptome. In diesen Konsensus basierten Leitlinien haben Mitglieder der "International Working Group on Neurotransmitter Related Disorders (iNTD)" sowie Patientenvertreter die verfügbare Evidenz für die Diagnose und Behandlung von AADCD ausgewertet und evidenzbasierte Empfehlungen nach den Methoden von SIGN und GRADE formuliert. Stets im Bewusstsein der limitierten Evidenz haben wir praktische Empfehlungen für die klinische Diagnose, Labordiagnose, Bildgebung und EEG, medizinische und nicht medizinische Behandlung formuliert. Des Weiteren haben wir Themen identifiziert, die der weiteren Forschung bedürfen. Wir glauben, dass diese Leitlinie die Behandlung von Patienten mit AADCD verbessert und gleichzeitig das Bewusstsein für diese seltene Erkrankung geschärft wird. Spanish abstract La deficiencia de la descarboxilasa de aminoácidos aromáticos (AADCD) es una enfermedad neurometabólica minoritaria de herencia autosómica recesiva que causa un defecto grave de dopamina, serotonina, epinefrina y norepinefrina. El inicio de la enfermedad es precoz, y sus síntomas principales incluyen hipotonía, trastornos del movimiento (crisis oculógiras, distonía e hipocinesia), retraso del desarrollo y signos disautonómicos. En esta guía de consenso han participado representantes del grupo de trabajo internacional sobre trastornos de la neurotransmisión (iNTD) y representantes de las asociaciones de pacientes, que han evaluado todas las evidencias existentes en relación al diagnóstico y tratamiento de la AADCD. Las recomnedaciones se han realizado siguiendo la metodología SIGN y GRADE. A pesar de los bajos niveles de evidencia existentes, se han podido establecer recomendaciones prácticas y que pueden ser muy útiles sobre el diagnóstico clínico y de laboratorio, las pruebas de neuroimagen y electroencefalográficas y sobre tratamientos tanto médicos como de soporte. Se han identificado además temas que pueden ser interesantes a desarrollar en el campo de la investigación de la AADCD. En conclusión, pensamos que esta guía aumentará la calidad en los cuidados de los pacientes con AADCD en todo el mundo, y que aumentará el conocimiento de esta rara enfermedad.